1992
DOI: 10.1111/j.1365-2303.1992.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Cervical Cancer In Ethiopian Women

Abstract: In common with many African countries, Ethiopia has a very limited cytological service, smears are only taken in a hospital or clinic setting and until very recently most had to be sent abroad for analysis. We describe the results of a clinical and cytological investigation of 2111 women attending hospitals and clinics in Addis Ababa: 33 invasive or microinvasive cancers and 10 dysplasias (CIN) were detected. The prevalence of invasive cervical cancer in that population was 15.6/1000. Risk factors were shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…The time for single trip to reach health services varies from minimum of twelve minutes to maximum of ninety six hours (with mean (SD) and median of 5.7 [9] and 3 hours respectively.…”
Section: Outpatient Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time for single trip to reach health services varies from minimum of twelve minutes to maximum of ninety six hours (with mean (SD) and median of 5.7 [9] and 3 hours respectively.…”
Section: Outpatient Costsmentioning
confidence: 99%
“…Similar studies in Addis Ababa and Yirgalem Hospital (Southern Ethiopia) have also shown that it accounted for 32% [7] and 25.8% [8] of female malignancies, respectively. A study done on 2,111 women attending hospitals and clinics in Addis Ababa has also reported the prevalence of invasive cancer to be 15.6/1000 of the studied population [9]. …”
Section: Introductionmentioning
confidence: 99%
“…8,15 In addition, Asian women working in the commercial sex industry in Sydney use condoms less often and have a higher incidence of STIs than their Caucasian counterparts. 16 Consequently, the failure of these women to opt on to the PTR in the medium term may result in an increase in cervical abnormalities and possibly cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18 It is the most common cancer in South African women. 2,6,7,16,18,19,22 Of all cancer deaths in South African black females, 38% are due to cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18 It is the most common cancer in South African women. 2,6,7,16,18,19,22 Of all cancer deaths in South African black females, 38% are due to cervical cancer. 19 A previous study of detection rates by cervical cancer screening, conducted on a high-risk population in the Johannesburg area, yielded detection rates of 28/1,000 for cervical intraepithelial neoplasia grade 3 and 13/1,000 for invasive squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%